Roughening of copper foil, copper-clad laminates and printed circuit boards
By fine roughening treatment on the copper foil surface, the ratio of Spk/Ssk and S10z/Ssk is controlled, and the problems of high transmission loss and insufficient adhesion in the printed circuit board are solved, and excellent transmission characteristics and high peel strength are achieved.
Patent Information
- Application Number
- CN202180023459.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-23
- Filing Date
- 2021-03-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-03-16
AI Technical Summary
In the manufacturing of printed circuit boards, the transmission loss of the roughened copper foil is high, resulting in high-frequency signal deterioration, and the adhesion between the copper foil and the insulating resin substrate is insufficient, and the peel strength is low.
By fine roughening treatment on the surface of the copper foil, the ratio of the protruding peak height Spk to the skewness Ssk (Spk/Ssk) and the ratio of the ten-point area height S10z to the skewness Ssk (S10z/Ssk) are controlled within a specific range, ensuring that the corrugation component of the copper foil is removed, thereby improving the transmission characteristics and peel strength.
It realizes excellent transmission characteristics and high peel strength in printed circuit boards, solving the problems of high transmission loss and insufficient adhesion.
Smart Images

Figure CN115413301B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a roughened copper foil, a copper-clad laminate and a printed circuit board. Background Art
[0002] In the manufacturing process of printed circuit boards, copper foil is widely used in the form of a copper-clad laminate bonded to an insulating resin substrate. In order to prevent the stripping of wiring during the manufacture of printed circuit boards, it is desired that the copper foil and the insulating resin substrate have a high adhesion. Therefore, in the conventional copper foil for printed circuit board manufacturing, the bonding surface of the copper foil is roughened to form a concave-convex surface containing fine copper particles, and the concave-convex surface is pressed into the interior of the insulating resin substrate to exert an anchoring effect, thereby improving the adhesion.
[0003] As a copper foil subjected to such a roughening treatment, for example, Patent Document 1 (Japanese Patent Gazette No. 2018-172785) discloses a surface-treated copper foil, which has a copper foil and a roughening treatment layer on at least one surface of the copper foil, the skewness Ssk of the side surface of the roughening treatment layer is greater than -0.6 and less than -0.35, and the glossiness of the TD (width direction) of the side surface of the roughening treatment layer is less than 70%. With such a surface-treated copper foil, the falling off of the roughening particles provided on the surface of the copper foil can be well suppressed, and the generation of wrinkles and stripes when bonded to an insulating substrate can be well suppressed. In addition, Patent Document 1 also discloses a surface-treated copper foil, wherein, for the purpose of obtaining the above-mentioned effect, the height Spk of the protruding peak on the side surface of the roughening treatment layer is greater than 0.13 μm and less than 0.27 μm.
[0004] On the other hand, with the recent high functionality of portable electronic devices, for high-speed processing of large-capacity data, the high frequency of signals, whether signals or simulations, is developing, and printed circuit boards suitable for high-frequency applications are required. For such high-frequency printed circuit boards, in order to be able to transmit high-frequency signals without deteriorating them, it is expected that the transmission loss will be reduced. The printed circuit board has a copper foil processed into a wiring pattern and an insulating substrate. As the main losses in the transmission loss, the conductor loss caused by the copper foil and the dielectric loss caused by the insulating substrate can be listed.
[0005] In this regard, a roughened copper foil is proposed to achieve a reduction in transmission loss. For example, Patent Document 2 (Japanese Patent Publication No. 2015-148011) discloses that, for the purpose of providing a surface-treated copper foil with low signal transmission loss and a laminate using the same, the skewness Rsk of the copper foil surface based on JIS B0601-2001 is controlled within a prescribed range of -0.35 or more and 0.53 or less by surface treatment.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2018-172785
[0009] Patent Document 2: Japanese Patent Application Publication No. 2015-148011 Summary of the invention
[0010] As mentioned above, in recent years, it is required to improve the transmission characteristics (high frequency characteristics) of printed circuit boards. In order to cope with such requirements, a more fine roughening treatment is attempted on the joint surface of the copper foil and the insulating resin substrate. That is, in order to reduce the concavo-convexity of the copper foil surface, which is the main factor that increases the transmission loss, it is considered to perform a fine roughening treatment on the surface of the copper foil with small corrugation (for example, the surface of the double-sided smooth foil, the electrode surface of the electrolytic copper foil). However, when using this roughened copper foil for processing copper-clad laminates and / or manufacturing printed circuit boards, problems such as low peel strength between the copper foil and the substrate and poor sealing reliability generally occur.
[0011] The inventors of the present invention have obtained the following insight: in the surface of a roughened copper foil, by controlling the ratio of the protruding peak height Spk or the ten-point area height S10z under the condition where the waviness component of the copper foil is removed to the skewness Ssk (Spk / Ssk or S10z / Ssk), and the ten-point area height S10z under the condition where the waviness component of the copper foil is reflected, respectively, within a prescribed range, it is possible to achieve both excellent transmission characteristics and high peel strength in a copper-clad laminate and / or printed circuit board manufactured using the same.
[0012] Therefore, an object of the present invention is to provide a roughened copper foil which can achieve both excellent transmission characteristics and high peel strength when used for a copper-clad laminate and / or a printed wiring board.
[0013] According to one embodiment of the present invention, there is provided a roughened copper foil having a roughened surface on at least one side.
[0014] The ratio of the protruding peak height Spk (μm) of the roughened surface measured according to ISO25178 under the conditions of a cutoff wavelength of 0.3 μm based on the S filter and a cutoff wavelength of 5 μm based on the L filter to the skewness Ssk measured according to ISO25178 under the conditions of a cutoff wavelength of 0.3 μm based on the S filter and a cutoff wavelength of 5 μm based on the L filter, that is, the particle front end diameter index Spk / Ssk is greater than 0.20 and less than 1.00, and the ten-point area height S10z measured according to ISO25178 under the conditions of a cutoff wavelength of 0.3 μm based on the S filter and a cutoff wavelength of 64 μm based on the L filter is greater than 2.50 μm.
[0015] According to another aspect of the present invention, there is provided a roughened copper foil having a roughened surface on at least one side.
[0016] The ratio of the ten-point area height S10z (μm) of the roughened surface measured according to ISO25178 under the conditions of a cutoff wavelength of 0.3 μm based on the S filter and a cutoff wavelength of 5 μm based on the L filter to the skewness Ssk measured according to ISO25178 under the conditions of a cutoff wavelength of 0.3 μm based on the S filter and a cutoff wavelength of 5 μm based on the L filter, that is, the particle tip roughness index S10z / Ssk is greater than 1.00 and less than 6.00, and the ten-point area height S10z measured according to ISO25178 under the conditions of a cutoff wavelength of 0.3 μm based on the S filter and a cutoff wavelength of 64 μm based on the L filter is greater than 2.50 μm.
[0017] According to another embodiment of the present invention, there is provided a copper-clad laminate including the roughened copper foil.
[0018] According to another embodiment of the present invention, there is provided a printed circuit board including the roughened copper foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1A This is a diagram for explaining the skewness Ssk determined in accordance with ISO 25178, and is a diagram showing a surface and its height distribution when Ssk<0.
[0020] Figure 1B This is a diagram for explaining the skewness Ssk determined in accordance with ISO25178, and is a diagram showing a surface and its height distribution when Ssk>0.
[0021] Figure 2 This is a diagram for explaining the load curve and load area ratio determined in accordance with ISO25178.
[0022] Figure 3 This is a diagram for explaining a load area ratio Smr1 separating a protruding peak portion from a center portion and a load area ratio Smr2 separating a protruding valley portion from a center portion, which are determined in accordance with ISO25178.
[0023] Figure 4 This is a diagram for explaining the pole height Sxp determined in accordance with ISO25178.
[0024] Figure 5 This is a diagram for explaining a case where the surface irregularities of the roughened copper foil include a roughening particle component and a waviness component.
[0025] Figure 6 This is a schematic diagram showing an example of the roughened copper foil of the present invention. DETAILED DESCRIPTION
[0026] definition
[0027] Definitions of terms and / or parameters used to define the present invention are shown below.
[0028] In this specification, "skewness Ssk" refers to a parameter indicating the symmetry of the height distribution measured in accordance with ISO25178. When this value is 0, it means that the height distribution is symmetrical in the upper and lower parts. Figure 1A As shown in , when this value is less than 0, it indicates a surface with many fine valleys. Figure 1B As shown, when this value is greater than 0, it indicates a surface with many fine peaks.
[0029] In this specification, the "surface load curve" (hereinafter referred to as "load curve") refers to a curve indicating the height of the load area ratio from 0% to 100% measured in accordance with ISO25178. Figure 2 The following are parameters that represent the area of the area above a certain height c. The load area ratio at height c is equivalent to Figure 2 Smr(c) in Figure 3 As shown in FIG. 1 , a secant of the load curve is drawn from the load area ratio of 0% with the load area ratio difference set to 40%, and the secant of the load curve is moved from the load area ratio of 0%. The position where the slope of the secant is the most gentle is called the central part of the load curve. With respect to the central part, the straight line with the smallest sum of squares of deviations from the vertical axis direction is called the equivalent straight line. The portion of the equivalent straight line within the range of heights from 0% to 100% of the load area ratio is called the central part. The portion higher than the central part is called the protruding peak, and the portion lower than the central part is called the protruding valley.
[0030] In this specification, the "protruding peak height Spk" means the average height of the protruding peak located at the center portion measured in accordance with ISO25178.
[0031] In this specification, "pole height Sxp" means: Figure 4 The parameter shown represents the height difference between the load area ratio p% and the load area ratio q% measured according to ISO 25178. Sxp represents the height difference between the surface average surface and the peak portion of the surface after removing the particularly high peaks on the surface. In this specification, Sxp adopts the height difference between the load area ratio of 2.5% and the load area ratio of 50%.
[0032] In this specification, "ten-point area height S10z" refers to: among the peaks and valleys within the reference area, the sum of the average height of the peaks from the highest peak to the 5th highest peak and the average depth (positive value) of the valleys from the deepest valley to the 5th deepest valley.
[0033] In this specification, "interface extension area ratio Sdr" refers to a parameter that indicates how much the extension area (surface area) of a defined region increases relative to the area of the defined region as a percentage, measured in accordance with ISO 25178. The smaller the value, the closer the surface shape is to being flat, and the Sdr of a completely flat surface is 0%. On the other hand, the larger the value, the more concave and convex the surface shape is.
[0034] In this specification, "particle tip diameter index Spk / Ssk" refers to the ratio of the protruding peak height Spk (μm) to the skewness Ssk. In addition, "particle tip roughness index S10z / Ssk" refers to the ratio of the ten-point area height S10z (μm) to the skewness Ssk.
[0035] The skewness Ssk, protruding peak height Spk, pole height Sxp, ten-point area height S10z and interface expansion area ratio Sdr can be calculated separately by measuring the surface profile of a specified measurement area (e.g., a two-dimensional area of 129.419 μm×128.704 μm) in the roughened surface using a commercially available laser microscope.
[0036] In this specification, the skewness Ssk, the protruding peak height Spk, and the pole height Sxp are measured under the conditions of a cutoff wavelength of 0.3 μm based on the S filter and a cutoff wavelength of 5 μm based on the L filter. In addition, in this specification, the interface expansion area ratio Sdr is measured under the conditions of a cutoff wavelength of 0.3 μm based on the S filter and a cutoff wavelength of 64 μm based on the L filter. Furthermore, in this specification, regarding the ten-point area height S10z, when used to calculate the particle front end roughness S10z / Ssk, it is measured under the conditions of a cutoff wavelength of 0.3 μm based on the S filter and a cutoff wavelength of 5 μm based on the L filter (hereinafter, the ten-point area height S10z measured under these conditions is sometimes referred to as "ten-point area height S10z (roughened particle S10z)" as needed). On the other hand, in cases other than for calculating the particle tip roughness S10z / Ssk, the ten-point area height S10z is measured under the conditions of a cutoff wavelength of 0.3 μm based on the S filter and a cutoff wavelength of 64 μm based on the L filter (hereinafter, the ten-point area height S10z measured under these conditions is sometimes referred to as "ten-point area height S10z (overall S10z)" as needed).
[0037] In this specification, the "electrode surface" of the electrolytic copper foil refers to the surface on the side in contact with the cathode during the production of the electrolytic copper foil.
[0038] In this specification, the "deposition surface" of the electrolytic copper foil refers to the surface on the side where the electrolytic copper is deposited during the production of the electrolytic copper foil, that is, the surface on the side not in contact with the cathode.
[0039] Roughened copper foil
[0040] The copper foil of the present invention is a roughened copper foil. The roughened copper foil has a roughened surface on at least one side. For the roughened surface, the ratio of the protruding peak height Spk (μm) to the skewness Ssk, that is, the particle front end diameter index Spk / Ssk is greater than 0.20 and less than 1.00, and the ten-point area height S10z (overall S10z) is greater than 2.50μm, and / or, the ten-point area height S10z (roughened particles S10z) (μm) is greater than the skewness Ssk, that is, the particle front end roughness index S10z / Ssk is greater than 1.00 and less than 6.00, and the ten-point area height S10z (overall S10z) is greater than 2.50μm. Thus, in the roughened copper foil, by controlling the Spk / Ssk or S10z / Ssk under the condition where the waviness component of the copper foil is removed, and the S10z under the condition where the waviness component of the copper foil is reflected, respectively, within the specified range, the copper-clad laminate and / or printed circuit board manufactured using the same can have both excellent transmission characteristics (high-frequency characteristics) and high peel strength (e.g., normal peel strength and peel strength after heat load).
[0041] It is difficult to achieve both excellent transmission characteristics and high peel strength. This is because: in order to obtain excellent transmission characteristics, the surface roughness of the copper foil needs to be reduced, while in order to obtain high peel strength, the surface roughness of the copper foil needs to be increased. The two are in a trade-off relationship. Figure 5 As shown in FIG. 1 , the concavity and convexity of the roughened copper foil surface include a "roughened particle component" and a "waviness component" with a longer period than the roughened particle component. In order to obtain excellent transmission characteristics, it is generally considered to perform fine roughening treatment on the surface of the copper foil with small waviness (such as the surface of a double-sided smooth foil, the electrode surface of an electrolytic copper foil) to form small roughened particles. However, when such a roughened copper foil is used to manufacture a copper-clad laminate and / or a printed circuit board, the peel strength between the copper foil and the substrate is generally reduced.
[0042] In response to this problem, the inventors of the present invention have studied the effects of the roughened particles and waviness of the concave and convex surfaces of the copper foil on the transmission characteristics and peel strength. As a result, it was found that the waviness component of the copper foil was contrary to expectations and was not easy to affect the transmission characteristics. It was mainly the size of the roughened particles that affected the transmission characteristics. Therefore, the inventors of the present invention found out that by combining the skewness Ssk and the protruding peak height Spk (roughened particles S10z) under the condition of removing the waviness component of the copper foil for evaluation, the front end diameter and / or front end roughness of the tiny particles (roughened particles) that will affect the transmission characteristics can be correctly evaluated. Specifically, it was found that by setting the particle front end diameter index Spk / Ssk or the particle front end roughness index S10z / Ssk of the roughened surface of the roughened copper foil to the above range, excellent transmission characteristics can be achieved. Furthermore, it was found that by setting the ten-point area height S10z (overall S10z) under the condition reflecting the waviness component of the copper foil within the above range, even small roughening particles that originally had difficulty in ensuring peel strength can achieve high peel strength between the copper foil and the substrate by utilizing the waviness of the copper foil. Thus, the roughened copper foil according to the present invention can achieve both excellent transmission characteristics and high peel strength when used for copper-clad laminates and / or printed circuit boards.
[0043] The roughening particle component and the waviness component on the surface of the copper foil can be distinguished by using the S filter and the L filter of the laser microscope. Specifically, by measuring the roughening surface of the roughened copper foil under the conditions of a cutoff wavelength of 0.3 μm based on the S filter and a cutoff wavelength of 5 μm based on the L filter, the parameters of the roughening particle component without the influence of the waviness component can be obtained. Therefore, it can be said that the skewness Ssk, the protruding peak height Spk, the pole height Sxp, the ten-point area height S10z (roughening particle S10z), the particle front end diameter index Spk / Ssk, and the particle front end roughness index S10z / Ssk in the present invention accurately reflect the parameters of the roughening particles on the surface of the copper foil. In contrast, by measuring the copper foil surface under the conditions of a cutoff wavelength of 0.3 μm based on the S filter and a cutoff wavelength of 64 μm based on the L filter, the overall parameters reflecting the influence of both the roughening particle component and the waviness component can be obtained. Therefore, the interface expansion area ratio Sdr and the ten-point region height S10z (overall S10z) in the present invention can be said to be parameters that reflect not only the roughening particle component but also the waviness component of the copper foil surface.
[0044] According to one embodiment of the present invention, for the roughened copper foil, the particle tip diameter index Spk / Ssk of the roughened surface is 0.20 μm or more and 1.00 μm or less, preferably 0.30 μm or more and 0.90 μm or less, more preferably 0.40 μm or more and 0.80 μm or less, and particularly preferably 0.50 μm or more and 0.75 μm or less. In addition, the skewness Ssk of the roughened surface of the roughened copper foil is preferably 0.40 or more and 1.20 or less, more preferably 0.45 or more and 1.17 or less, further preferably 0.50 or more and 1.14 or less, and particularly preferably 0.55 μm or more and 1.10 μm or less. Furthermore, the height of the protruding peak Spk of the roughened surface of the roughened copper foil is preferably 0.25 μm or more and 0.80 μm or less, more preferably 0.40 μm or more and 0.80 μm or less, further preferably 0.40 μm or more and 0.78 μm or less, and particularly preferably 0.42 μm or more and 0.76 μm or less. As described above, the skewness Ssk, the height of the protruding peak Spk, and the particle front end diameter index Spk / Ssk in the present invention remove the influence of the corrugation component of the unevenness of the copper foil surface, so that the accurate value of the small front end diameter of the roughened particles that affects the transmission characteristics can be measured. In this regard, when the skewness Ssk, the height of the protruding peak Spk, and / or the particle front end diameter index Spk / Ssk are within the above range, the peel strength is high and better transmission characteristics can be achieved.
[0045] According to another embodiment of the present invention, for the roughened copper foil, the particle tip roughness index S10z / Ssk of the roughened surface is 1.00 μm or more and 6.00 μm or less, preferably 1.50 μm or more and 6.00 μm or less, more preferably 2.00 μm or more and 6.00 μm or less, and particularly preferably 2.00 μm or more and 5.50 μm or less. In addition, the skewness Ssk of the roughened surface of the roughened copper foil is preferably 0.40 or more and 1.20 or less, more preferably 0.45 or more and 1.17 or less, further preferably 0.50 or more and 1.14 or less, and particularly preferably 0.55 μm or more and 1.10 μm or less. Furthermore, the ten-point area height S10z (roughened particles S10z) of the roughened surface of the roughened copper foil is preferably 1.50 μm or more and 4.00 μm or less, more preferably 2.00 μm or more and 4.00 μm or less, further preferably 2.20 μm or more and 3.80 μm or less, particularly preferably 2.30 μm or more and 3.60 μm or less, and most preferably 2.40 μm or more and 3.40 μm or less. As described above, the skewness Ssk, the ten-point area height S10z (roughened particles S10z), and the particle tip roughness index S10z / Ssk in the present invention remove the influence of the corrugation component of the concave and convex surface of the copper foil, and therefore, the correct value of the minute tip roughness of the roughened particles that affects the transmission characteristics can be measured. In this regard, when the skewness Ssk, the ten-point area height S10z (roughened particle S10z), and / or the particle tip roughness index S10z / Ssk are within the above ranges, high peel strength is achieved and more excellent transmission characteristics can be achieved.
[0046] The ten-point area height S10z (overall S10z) of the roughened surface of the roughened copper foil is 2.50 μm or more, preferably 2.50 μm or more and 10.00 μm or less, more preferably 2.90 μm or more and 9.00 μm or less, further preferably 3.30 μm or more and 8.00 μm or less, and particularly preferably 3.70 μm or more and 7.00 μm or less. The ten-point area height S10z (overall S10z) reflects the waviness component of the concavity and convexity of the copper foil surface. As mentioned above, when the ten-point area height S10z (overall S10z) is within the above range, it is an excellent transmission characteristic, and the waviness of the copper foil can be used to achieve a high peel strength between the copper foil and the substrate.
[0047] The interface expansion area ratio Sdr of the roughened copper foil is preferably 22.00% or more, more preferably 25.00% or more, further preferably 30.00%, further more preferably 34.00% or more and 130.00% or less, particularly preferably 37.00% or more and 100.00% or less, and most preferably 40.00% or more and 60.00% or less. When the interface expansion area ratio Sdr is within the above range, the dielectric properties are excellent, and the roughened surface has a shape rich in concave and convex suitable for achieving higher peel strength.
[0048] The peak height Sxp of the roughened copper foil is preferably 0.40 μm or more and 1.60 μm or less, more preferably 0.50 μm or more and 1.60 μm or less, further preferably 0.60 μm or more and 1.60 μm or less, further preferably 0.60 μm or more and 1.30 μm or less, particularly preferably 0.60 μm or more and 1.20 μm or less, and most preferably 0.60 μm or more and 1.10 μm or less. The peak height Sxp is the height difference between the average surface of the surface and the peak of the surface. When the peak height Sxp is within the above range, the anchoring effect is effectively exerted, thereby achieving a higher peel strength.
[0049] The thickness of the roughened copper foil is not particularly limited, but is preferably 0.1 μm to 35 μm, and more preferably 0.5 μm to 18 μm. It should be noted that the roughened copper foil of the present invention is not limited to the roughened copper foil having the surface of the ordinary copper foil roughened, but may also be the roughened copper foil having the surface of the copper foil with carrier copper foil roughened and / or finely roughened.
[0050] Figure 6 An example of the roughened copper foil of the present invention is shown in FIG. Figure 6 As shown, the roughened copper foil of the present invention is preferably manufactured by roughening the surface of a copper foil with a specified waviness (e.g., the precipitation surface of an electrolytic copper foil) under desired low roughening conditions to form fine roughened particles. Therefore, according to a preferred embodiment of the present invention, the roughened copper foil is an electrolytic copper foil, and the roughened surface exists on the side of the electrolytic copper foil opposite to the electrode surface (i.e., the precipitation surface side). It should be noted that the roughened copper foil may have a roughened surface on both sides, or may have a roughened surface on only one side. The roughened surface typically has a plurality of roughened particles, and the plurality of roughened particles are preferably each formed by copper particles. The copper particles may be formed of metallic copper or of a copper alloy.
[0051] The roughening treatment for forming the roughening surface is preferably carried out by forming roughening particles using copper or copper alloy on the copper foil. The copper foil before the roughening treatment can be a copper foil without roughening, or a copper foil that has been pre-roughened. The ten-point height Rz of the microscopic roughness of the surface of the roughened copper foil measured according to JIS B0601-1994 is preferably 1.50 μm or more and 10.00 μm or less, more preferably 2.00 μm or more and 8.00 μm or less. When it is within the above range, it is easy to give the roughening surface the surface profile required by the roughening copper foil of the present invention.
[0052] The roughening treatment is preferably carried out at a temperature of 20° C. to 40° C. in a copper sulfate solution having a copper concentration of 5 g / L to 20 g / L and a sulfuric acid concentration of 50 g / L to 200 g / L. 2 Above and 50A / dm 2 The electrolytic deposition is preferably carried out for 0.5 seconds to 30 seconds, more preferably for 1 second to 30 seconds, and further preferably for 1 second to 3 seconds. In addition, as another example, in the case of adding 9-phenylacridine (9PA), it is preferred that in a copper sulfate solution containing copper and sulfuric acid at the above concentration, and containing a chlorine concentration of 20 mg / L to 100 mg / L and 9PA of 100 mg / L to 200 mg / L, at a temperature of 20°C to 40°C, the electrolytic deposition is carried out at 20 A / dm 2 Above and 200A / dm 2 Electrolytic deposition is performed as follows. The electrolytic deposition is preferably performed for 0.3 seconds or more and 30 seconds or less, and more preferably for 0.5 seconds or more and 1.0 seconds or less. During electrolytic deposition, the interelectrode copper supply defined by the following formula is preferably set to 0.1 [(g·m) / (minute·L)] or more and 1.0 [(g·m) / (minute·L)] or less.
[0053] F Cu =F CuSO4 ×C Cu / S
[0054] (Where F Cu is the interelectrode copper supply [(g·m) / (min·L)], F CuSO4 is the flow rate of copper sulfate solution (m 3 / min), C Cu is the copper concentration of the copper sulfate solution (g / L), S is the cross-sectional area between the anode and cathode (m 2 ))
[0055] This makes it easy to give the surface profile required for the roughened copper foil of the present invention to the surface of the roughened copper foil. Of course, the roughened copper foil according to the present invention is not limited to the above method, and can be produced by any method.
[0056] According to the expectation, the roughening copper foil can be subjected to rust-proof treatment to form a rust-proof treatment layer. The rust-proof treatment preferably includes a plating treatment using zinc. The plating treatment using zinc can be any of a galvanizing treatment and a zinc alloy treatment, and the zinc alloy treatment is particularly preferably a zinc-nickel alloy treatment. The zinc-nickel alloy treatment can be a plating treatment containing at least Ni and Zn, and can also contain other elements such as Sn, Cr, Co, and Mo. For example, by making the rust-proof treatment layer further contain Mo on the basis of Ni and Zn, the adhesion, chemical resistance and heat resistance of the treated surface of the roughening copper foil to the resin are more excellent, and etching residues are not easy to remain. The Ni / Zn adhesion ratio in the zinc-nickel alloy treatment is preferably 1.2 or more and 10 or less, more preferably 2 or more and 7 or less, and further preferably 2.7 or more and 4 or less in terms of mass ratio. In addition, the rust-proof treatment preferably also includes a chromate treatment, which is preferably performed on the surface of the coating containing zinc after the zinc plating treatment. Thus, the rust resistance can be further improved. A particularly preferred rust-proofing treatment is a combination of zinc-nickel alloy plating and subsequent chromate treatment.
[0057] As desired, the surface of the roughened copper foil may be treated with a silane coupling agent to form a silane coupling agent layer. This can improve moisture resistance, chemical resistance, and adhesion to adhesives, etc. The silane coupling agent layer can be formed by appropriately diluting and applying the silane coupling agent and drying it. Examples of silane coupling agents include epoxy-functional silane coupling agents such as 4-glycidylbutyltrimethoxysilane and 3-glycidoxypropyltrimethoxysilane; or amino-functional silane coupling agents such as 3-aminopropyltriethoxysilane, N-(2-aminoethyl)3-aminopropyltrimethoxysilane, N-3-(4-(3-aminopropoxy)butoxy)propyl-3-aminopropyltrimethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane. or 3-mercaptopropyltrimethoxysilane or other mercapto-functional silane coupling agents; or vinyltrimethoxysilane, vinylphenyltrimethoxysilane or other olefin-functional silane coupling agents; or 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane or other acrylic-functional silane coupling agents; or imidazole-functional silane coupling agents such as imidazole silane; or triazine-functional silane coupling agents such as triazine silane, etc.
[0058] Based on the above reasons, the roughened copper foil preferably further has an anti-rust treatment layer and / or a silane coupling agent layer on the roughened surface, and more preferably has both an anti-rust treatment layer and a silane coupling agent layer. The anti-rust treatment layer and the silane coupling agent layer can be formed not only on the roughened surface side of the roughened copper foil, but also on the side where the roughened surface is not formed.
[0059] Copper Clad Laminated Board
[0060] The roughened copper foil of the present invention is preferably used for the manufacture of copper-clad laminates for printed circuit boards. That is, according to a preferred embodiment of the present invention, a copper-clad laminate is provided, which has the above-mentioned roughened copper foil. By using the roughened copper foil of the present invention, the copper-clad laminate can take into account both excellent dielectric properties and high peel strength. The copper-clad laminate comprises: the roughened copper foil of the present invention, and a resin layer arranged in close contact with the roughened surface of the roughened copper foil. The roughened copper foil can be arranged on one side of the resin layer or on both sides. The resin layer comprises a resin, preferably an insulating resin. The resin layer is preferably a prepreg and / or a resin sheet. Prepreg is a general term for composite materials formed by impregnating synthetic resin into substrates such as synthetic resin plates, glass plates, glass woven fabrics, glass non-woven fabrics, and paper. As preferred examples of insulating resins, epoxy resins, cyanate resins, bismaleimide triazine resins (BT resins), polyphenylene ether resins, phenolic resins, etc. can be cited. In addition, as examples of insulating resins constituting the resin sheet, insulating resins such as epoxy resins, polyimide resins, and polyester resins can be cited. In addition, from the viewpoint of improving insulation, the resin layer may contain filler particles formed by various inorganic particles such as silica and alumina. The thickness of the resin layer is not particularly limited, preferably 1 μm or more and 1000 μm or less, more preferably 2 μm or more and 400 μm or less, and further preferably 3 μm or more and 200 μm or less. The resin layer may be composed of a plurality of layers. Resin layers such as prepregs and / or resin sheets may be arranged on the roughened copper foil via a primer resin layer pre-coated on the surface of the copper foil.
[0061] Printed Circuit Board
[0062] The roughened copper foil of the present invention is preferably used for the manufacture of printed circuit boards. That is, according to a preferred embodiment of the present invention, a printed circuit board is provided, which has the above-mentioned roughened copper foil. By using the roughened copper foil of the present invention, the printed circuit board can have both excellent transmission characteristics and high peel strength. The printed circuit board based on this embodiment comprises a layer structure stacked with a resin layer and a copper layer. The copper layer is a layer derived from the roughened copper foil of the present invention. In addition, for the resin layer, as described above with respect to the copper-clad laminate. In any case, the printed circuit board can adopt a known layer structure. As a specific example related to the printed circuit board, the single-sided or double-sided printed circuit board obtained by bonding the roughened copper foil of the present invention to one or both sides of the prepreg and curing to form a laminate and then forming a circuit, and the multilayer printed circuit board formed by multilayering them, etc. can be listed. In addition, as other specific examples, flexible printed circuit boards, COFs, TAB tapes, etc., which form circuits by forming the roughened copper foil of the present invention on a resin film, can also be listed. As other specific examples, there can be listed: a resin-coated copper foil (RCC) formed by coating the above-mentioned resin layer on the roughened copper foil of the present invention, a build-up wiring board in which a circuit is formed by a modified semi-additive (MSAP) method, a subtractive method, or the like after laminating the resin layer as an insulating adhesive layer on the above-mentioned printed circuit board, a build-up wiring board in which the roughened copper foil is removed and a circuit is formed by a semi-additive (SAP) method, a direct build-up wafer in which lamination of resin-coated copper foil on a semiconductor integrated circuit and circuit formation are repeated alternately, and the like.
[0063] Example
[0064] The present invention is described in more detail by the following examples.
[0065] Examples 1 to 18
[0066] The roughened copper foil of the present invention is produced as follows.
[0067] (1) Manufacturing of electrolytic copper foil
[0068] For Examples 1 to 9 and 11 to 18, a sulfuric acid copper sulfate solution of the composition shown below was used as the copper electrolyte, a titanium electrode was used as the cathode, and a DSA (dimensional stability anode) was used as the anode. The solution temperature was 45° C. and the current density was 55 A / dm 2 Electrolysis was performed to obtain electrolytic copper foil A having a thickness shown in Table 1. At this time, an electrode whose surface was polished with a #1000 buff to adjust the surface roughness was used as a cathode.
[0069] <Composition of sulfuric acid-acid copper sulfate solution>
[0070] -Copper concentration: 80g / L
[0071] - Sulfuric acid concentration: 300g / L
[0072] - Gelatin concentration: 5mg / L
[0073] -Chlorine concentration: 30mg / L
[0074] On the other hand, in Example 10, a sulfuric acid-based copper sulfate solution having the composition shown below was used as the copper electrolyte to obtain an electrolytic copper foil B having the thickness shown in Table 1. At this time, the conditions other than the composition of the sulfuric acid-based copper sulfate solution were the same as those of the electrolytic copper foil A.
[0075] <Composition of sulfuric acid-acid copper sulfate solution>
[0076] -Copper concentration: 80g / L
[0077] - Sulfuric acid concentration: 260g / L
[0078] - Bis(3-sulfopropyl) disulfide concentration: 30mg / L
[0079] -Diallyldimethylammonium chloride polymer concentration: 50mg / L
[0080] -Chlorine concentration: 40mg / L
[0081] (2) Roughening treatment
[0082] Among the electrode surface and the deposition surface of the electrolytic copper foil, the deposition surface side was roughened for Examples 1 to 11 and 15 to 18, and the electrode surface side was roughened for Examples 12 to 14. It should be noted that the microscopic roughness ten-point height Rz measured in accordance with JIS B0601-1994 for the deposition surface of the electrolytic copper foil used in Examples 1 to 11 and 15 to 18 and the electrode surface of the electrolytic copper foil used in Examples 12 to 14 is shown in Table 1.
[0083] For Examples 1 to 9 and 14 to 17, the roughening treatment (first roughening treatment) shown below was performed. The roughening treatment was performed by electrolyzing each example under the conditions of current density, time and interelectrode copper supply amount shown in Table 1 in a copper electrolytic solution for roughening treatment (copper concentration: 5 g / L or more and 20 g / L or less, sulfuric acid concentration: 50 g / L or more and 200 g / L or less, liquid temperature: 30°C) and washing with water.
[0084] For Examples 10 to 13, the first roughening treatment, the second roughening treatment, and the third roughening treatment described below were performed in this order.
[0085] - The first roughening treatment was performed by electrolyzing in a copper electrolytic solution for roughening treatment (copper concentration: 5 g / L to 20 g / L, sulfuric acid concentration: 50 g / L to 200 g / L, liquid temperature: 30°C) under the conditions of current density, time and inter-electrode copper supply amount shown in Table 1.
[0086] The second roughening treatment was performed by electrolyzing in a copper electrolytic solution for roughening treatment with the same composition as that of the first roughening treatment under the conditions of current density, time and inter-electrode copper supply amount shown in Table 1 and then washing with water.
[0087] - The third roughening treatment was performed by electrolyzing in a copper electrolytic solution for roughening treatment (copper concentration: 65 g / L to 80 g / L, sulfuric acid concentration: 50 g / L to 200 g / L, liquid temperature: 45°C) under the conditions of current density, time and inter-electrode copper supply amount shown in Table 1 and washing with water.
[0088] For Example 18, the roughening treatment (first roughening treatment) shown below was performed. The roughening treatment was performed by electrolyzing and washing with water in a copper electrolytic solution for roughening treatment (copper concentration: 5 g / L or more and 20 g / L or less, sulfuric acid concentration: 50 g / L or more and 200 g / L or less, chlorine concentration 20 mg / L or more and 100 mg / L or less, 9PA 100 mg / L or more and 200 mg / L or less, liquid temperature: 30° C.) under the conditions of current density, time and interelectrode copper supply amount shown in Table 1.
[0089] (3) Anti-rust treatment
[0090] The roughened electrolytic copper foil was subjected to the rust-proof treatment shown in Table 1. For the rust-proof treatment, for Examples 1 to 7 and 9 to 18, a pyrophosphate bath was used on both sides of the electrolytic copper foil at a potassium pyrophosphate concentration of 80 g / L, a zinc concentration of 0.2 g / L, a nickel concentration of 2 g / L, a liquid temperature of 40°C, and a current density of 0.5 A / dm 2 On the other hand, for Example 8, the surface of the electrolytic copper foil subjected to the roughening treatment was subjected to a rust prevention treatment at a potassium pyrophosphate concentration of 100 g / L, a zinc concentration of 1 g / L, a nickel concentration of 2 g / L, a molybdenum concentration of 1 g / L, a liquid temperature of 40°C, and a current density of 0.5 A / dm 2 Zinc-nickel based rust-proofing treatment was performed. The surface of the electrolytic copper foil of Example 8 opposite to the surface subjected to the roughening treatment was subjected to zinc-nickel based rust-proofing treatment under the same conditions as in Examples 1 to 7 and 9 to 18.
[0091] (4) Chromate treatment
[0092] The electrolytic copper foil subjected to the above rust-proof treatment was subjected to chromate treatment on both sides to form a chromate layer on the rust-proof treatment layer. The chromate treatment was carried out at a chromic acid concentration of 1 g / L, pH 11, liquid temperature 25°C and current density 1 A / dm 2 under the conditions of.
[0093] (5) Silane coupling agent treatment
[0094] The copper foil subjected to the above-mentioned chromate treatment is washed with water and then immediately subjected to a silane coupling agent treatment so that the silane coupling agent is adsorbed on the chromate layer of the roughened surface. The silane coupling agent treatment is performed by spraying a silane coupling agent solution with pure water as a solvent onto the roughened surface for adsorption treatment. As the silane coupling agent, 3-aminopropyltrimethoxysilane is used in Examples 1 to 5, 9 and 14 to 18, 3-glycidoxypropyltrimethoxysilane is used in Examples 6 and 10 to 13, 3-acryloxypropyltrimethoxysilane is used in Example 7, and vinyltrimethoxysilane is used in Example 8. The concentration of the silane coupling agent is set to 3 g / L. After the adsorption of the silane coupling agent, the water is finally evaporated by an electric heater to obtain a roughened copper foil of a specified thickness.
[0095] [Table 1]
[0096]
[0097] evaluate
[0098] The produced roughened copper foil was subjected to various evaluations shown below.
[0099] (a) Surface properties parameters of the roughened surface
[0100] The roughened surface of the roughened copper foil was measured according to ISO25178 by using a surface roughness analysis using a laser microscope (manufactured by Olympus Corporation, OLS-5000). Specifically, the surface profile of the 129.419 μm × 128.704 μm area in the roughened surface of the roughened copper foil was measured using the above-mentioned laser microscope with an objective lens magnification of 100 times. The surface profile of the obtained roughened surface was analyzed according to the conditions shown in Table 2, and the skewness Ssk, the protruding peak height Spk, the ten-point area height S10z, the interface extension area ratio Sdr, and the pole height Sxp were calculated. It should be noted that for the ten-point area height S10z, the cutoff wavelength based on the L filter was set to 2 conditions (5 μm and 64 μm) and calculated separately. In addition, the particle tip diameter index Spk / Ssk and the particle tip roughness index S10z / Ssk were calculated based on the obtained values of the skewness Ssk, the protruding peak height Spk, and the ten-point area height S10z (L filter: 5 μm).
[0101] [Table 2]
[0102] Table 2
[0103]
[0104] (b) Peel strength between copper foil and substrate
[0105] In order to evaluate the adhesion between the roughened copper foil in normal state and after heat loading and the insulating substrate, the normal peel strength and the peel strength after tin immersion (solder float) were measured as follows.
[0106] (b-1) Normal peel strength
[0107] As an insulating substrate, two prepregs (thickness 100 μm) containing polyphenylene ether, triallyl isocyanurate and bismaleimide resin as main components were prepared and stacked. The surface-treated copper foil was stacked on the stacked prepregs in such a way that its roughened surface was in contact with the prepregs. 2 , 205°C for 120 minutes to produce a copper-clad laminate. Next, the circuit is formed on the copper-clad laminate by etching to produce a test substrate with a straight circuit of 3 mm width. It should be noted that for Examples 9 and 16, before the circuit is formed, the copper foil side surface of the copper-clad laminate is etched until the thickness of the copper foil is 18 μm. The straight circuit thus obtained is peeled off from the insulating substrate according to the A method (90° peeling) of JIS C 5016-1994 and the normal peel strength (kgf / cm) is measured. The normal peel strength obtained is graded and evaluated according to the following criteria. The results are shown in Table 3.
[0108] <Normal peel strength evaluation criteria>
[0109] -Evaluation A: Normal peel strength is 0.42kgf / cm or more
[0110] -Evaluation B: Normal peel strength is 0.40 kgf / cm or more and less than 0.42 kgf / cm
[0111] -Evaluation C: Normal peel strength is less than 0.40kgf / cm
[0112] (b-2) Peel strength after tin immersion
[0113] Before the peel strength was measured, the test substrate with a straight circuit was immersed in a solder bath at 260°C for 20 seconds. The peel strength after tinning (kgf / cm) was measured by the same procedure as the normal peel strength. The peel strength after tinning obtained was graded and evaluated according to the following criteria. The results are shown in Table 3.
[0114] <Evaluation criteria for peel strength after tin immersion>
[0115] -Evaluation A: Peel strength after tin immersion is 0.41kgf / cm or more
[0116] -Evaluation B: Peel strength after tin immersion is 0.39 kgf / cm or more and less than 0.41 kgf / cm
[0117] -Evaluation C: Peel strength after tinning is less than 0.39kgf / cm
[0118] (c) Transmission characteristics
[0119] A high-frequency substrate (manufactured by Panasonic Corporation, MEGTRON6N) was prepared as an insulating resin substrate. The roughened copper foil was laminated on both sides of the insulating resin substrate in such a way that its roughened surface was in contact with the insulating resin substrate, and a vacuum press was used to laminate at a temperature of 190°C and a pressing time of 120 minutes to obtain a copper-clad laminate with an insulation thickness of 136 μm. Then, the copper-clad laminate was etched to obtain a substrate for measuring transmission loss in which a microstrip line was formed in such a way that the characteristic impedance became 50Ω. The transmission loss (dB / cm) of the obtained transmission loss measurement substrate was measured using a network analyzer (manufactured by Keysight Technologies, N5225B). The obtained transmission loss was graded and evaluated according to the following criteria. The results are shown in Table 3.
[0120] <Transmission loss evaluation criteria>
[0121] -Evaluation A: Transmission loss is -0.57dB / cm or more
[0122] - Rating B: Transmission loss is -0.70dB / cm or more and less than -0.57dB / cm
[0123] - Rating C: Transmission loss is less than -0.70dB / cm
[0124] [Table 3]
[0125]
Claims
1. A roughened copper foil having a roughened surface on at least one side. The roughened surface has a ratio of a protruding peak height Spk measured in accordance with ISO 25178 at a cutoff wavelength of 0.3 μm based on an S filter and a cutoff wavelength of 5 μm based on an L filter to a skewness Ssk measured in accordance with ISO 25178 at a cutoff wavelength of 0.3 μm based on an S filter and a cutoff wavelength of 5 μm based on an L filter, i.e., a particle tip diameter index Spk / Ssk of 0.20 or more and 1.00 or less, and a ten-point area height S10z measured in accordance with ISO 25178 at a cutoff wavelength of 0.3 μm based on an S filter and a cutoff wavelength of 64 μm based on an L filter is 2.50 μm or more. The unit of the protrusion peak height Spk is μm.
2. The roughened copper foil according to claim 1, wherein The roughened surface has an interface expansion area ratio Sdr of 22.00% or more, as measured in accordance with ISO 25178 under conditions of an S filter with a cutoff wavelength of 0.3 μm and an L filter with a cutoff wavelength of 64 μm.
3. The roughened copper foil according to claim 1 or 2, wherein The roughened surface has a skewness Ssk of 0.40 or more and 1.20 or less, as measured in accordance with ISO 25178 under conditions of an S filter with a cutoff wavelength of 0.3 μm and an L filter with a cutoff wavelength of 5 μm.
4. The roughened copper foil according to claim 1 or 2, wherein The roughened surface has a protruding peak height Spk of 0.25 μm to 0.80 μm, as measured in accordance with ISO 25178 using an S filter with a cutoff wavelength of 0.3 μm and an L filter with a cutoff wavelength of 5 μm.
5. The roughened copper foil according to claim 1 or 2, wherein The roughened surface has a ten-point area height S10z of 2.50 μm to 10.00 μm, as measured in accordance with ISO 25178 under conditions of an S filter with a cutoff wavelength of 0.3 μm and an L filter with a cutoff wavelength of 64 μm.
6. The roughened copper foil according to claim 1 or 2, wherein The roughened surface has a ten-point area height S10z of 1.50 μm to 4.00 μm, as measured in accordance with ISO 25178 under conditions of an S filter with a cutoff wavelength of 0.3 μm and an L filter with a cutoff wavelength of 5 μm.
7. The roughened copper foil according to claim 1 or 2, wherein The peak height Sxp of the roughened surface measured in accordance with ISO 25178 under the conditions of an S filter with a cutoff wavelength of 0.3 μm and an L filter with a cutoff wavelength of 5 μm is 0.40 μm or more and 1.60 μm or less. 8 . The roughened copper foil according to claim 1 , further comprising a rust-proofing layer and / or a silane coupling agent treatment layer on the roughened surface.
9. The roughened copper foil according to claim 1 or 2, wherein The roughened copper foil is an electrolytic copper foil, and the roughened surface is located on the side of the electrolytic copper foil opposite to the electrode surface.
10. A roughened copper foil having a roughened surface on at least one side. The roughened surface has a particle tip roughness index S10z / Ssk, which is a ratio of a ten-point area height S10z measured under conditions of an S filter cutoff wavelength of 0.3 μm and an L filter cutoff wavelength of 5 μm in accordance with ISO 25178 to a skewness Ssk measured under conditions of an S filter cutoff wavelength of 0.3 μm and an L filter cutoff wavelength of 5 μm in accordance with ISO 25178, of 1.00 or more and 6.00 or less, and a ten-point area height S10z measured under conditions of an S filter cutoff wavelength of 0.3 μm and an L filter cutoff wavelength of 64 μm in accordance with ISO 25178 of 2.50 μm or more. The unit of the ten-point area height S10z is μm.
11. The roughened copper foil according to claim 10, wherein The roughened surface has an interface expansion area ratio Sdr of 22.00% or more, as measured in accordance with ISO 25178 under conditions of an S filter with a cutoff wavelength of 0.3 μm and an L filter with a cutoff wavelength of 64 μm.
12. The roughened copper foil according to claim 10 or 11, wherein The roughened surface has a skewness Ssk of 0.40 or more and 1.20 or less, as measured in accordance with ISO 25178 under conditions of an S filter with a cutoff wavelength of 0.3 μm and an L filter with a cutoff wavelength of 5 μm.
13. The roughened copper foil according to claim 10 or 11, wherein The roughened surface has a protruding peak height Spk of 0.25 μm to 0.80 μm, as measured in accordance with ISO 25178 using an S filter with a cutoff wavelength of 0.3 μm and an L filter with a cutoff wavelength of 5 μm.
14. The roughened copper foil according to claim 10 or 11, wherein The roughened surface has a ten-point area height S10z of 2.50 μm to 10.00 μm, as measured in accordance with ISO 25178 under conditions of an S filter with a cutoff wavelength of 0.3 μm and an L filter with a cutoff wavelength of 64 μm.
15. The roughened copper foil according to claim 10 or 11, wherein The roughened surface has a ten-point area height S10z of 1.50 μm to 4.00 μm, as measured in accordance with ISO 25178 under conditions of an S filter with a cutoff wavelength of 0.3 μm and an L filter with a cutoff wavelength of 5 μm.
16. The roughened copper foil according to claim 10 or 11, wherein The peak height Sxp of the roughened surface measured in accordance with ISO 25178 under the conditions of an S filter with a cutoff wavelength of 0.3 μm and an L filter with a cutoff wavelength of 5 μm is 0.40 μm or more and 1.60 μm or less. 17 . The roughened copper foil according to claim 10 , further comprising a rust-proofing layer and / or a silane coupling agent treatment layer on the roughened surface.
18. The roughened copper foil according to claim 10 or 11, wherein The roughened copper foil is an electrolytic copper foil, and the roughened surface is located on the side of the electrolytic copper foil opposite to the electrode surface. 19 . A copper-clad laminate comprising the roughened copper foil according to claim 1 . 20 . A printed wiring board comprising the roughened copper foil according to claim 1 .
Citation Information
Patent Citations
Surface treated copper foil, laminate using the same, printed wiring board, electronic apparatus and method for manufacturing printed wiring board
JP2015148011A
Surface-treated copper foil, surface-treated copper foil with resin layer, copper foil with carrier, laminate, method for producing printed wiring board and method for producing electronic apparatus
JP2018172785A
Roughened copper foil, copper-clad laminate and printed wiring board
CN107614760A
Surface treated copper foil, copper foil with carrier, laminate, method for manufacturing printed wiring board, and method for manufacturing electronic device
CN108697006A